Pengaruh Metode Pengolahan dan Level Roasting Terhadap Karakteristik Kopi Robusta Argopuro Jember - Nuraisyah, Anni; Juliansyah, Alfian; Pramudianto, Pascal R; Prayogo, M. Mikail R P; Zulisma, Elok D; Diana, Luluk E; Alwi, Annisa Lutfi (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Jember, located in East Java, is renowned for its exceptional production of robusta coffee. The objective of this study was to analyze the physical properties of roasted robusta coffee beans sourced from Argopuro, Jember. The study utilized a fully Randomized Factorial Design incorporating two factors: processing method and roasting intensity. The processing method comprised four levels: natural process, honey process, semi-wet process, and full-wash process. Concurrently, the roasting level treatment consisted of three levels: light, medium, and dark. The observations encompassed the density of green beans, the density of roast beans, and the yield of roast beans. The green beans utilized in this investigation adhered to the quality criteria specified in the Indonesian National Standard (SNI) Grade 2. The research findings indicated that the processing technique had no substantial impact on the density of green beans. Neither the processing method nor the roasting level treatments had a different effect on the density or yield of the roasted beans. Nevertheless, the application of different roasting levels did result in a significant effect on both the density and yield of roasted coffee beans. The natural process approach yielded the maximum green bean density, weighing 365 kg/m3. The dark roast level resulted in the maximum bean density across all processing methods, including the natural, honey, semi-wet, and full-wash processes. The specific values for each method were 735.3 kg/m3, 637.3 kg/m3, 698.4 kg/m3, and 637.5 kg/m3, respectively. Moreover, the light roast level achieved the maximum output of roast beans, reaching 88.83%.